Peningkatan keterampilan mengonstruksi Teks Negosiasi melalui model Problem Based Learning pada Peserta Didik Kelas X MIPA 2 SMA Negeri 7 Malang - Wening Suryandari; Gigit Mujianto; Laili Ivana (BAHASTRA, 2019)
This study describes the application of the problem based learning (PBL) learning model as a solution to improve the skills of constructing the negotiating text of students of class X MIPA 2 Malang 7 High School. The purpose of this study is to describe the quality of the learning process in constructing negotiating texts using the problem based learning model, describing improvement in skills in constructing negotiating texts with problem based learning models, and describing changes in students' behavior after the learning process with problem based learning models. This class action research uses descriptive qualitative research design carried out in three stages, namely pre-cycle, cycle I and cycle II. The results showed that the application of the problem based learning (PBL) model was able to improve the skills of constructing the negotiating text of students of class X MIPA 2 Malang 7 High School. The ability of students to think critically when constructing text also increases. Through the problem based learning (PBL) learning model students are not taught to be wishful but directed to be able to solve their own problems through negotiations as outlined in a complete text in accordance with the structure and language of the negotiating text. Therefore, the application of the problem based learning (PBL) model was able to improve the skills of constructing the negotiation text by 7.22% in the first cycle and 14.50% in the second cycle and changing the behavior of students in a positive direction.